Parasitylenchus myiophagus n. sp. (Nematoda: Parasitylenchidae), a tylenchid nematode parasite of long-legged flies (Diptera: Dolichopodidae) - Poinar, George; Runyon, Justin B. (Zootaxa, 2021)
A tylenchid nematode parasite of a male long-legged fly, Tachytrechus sanus Osten Sacken (Diptera: Dolichopodidae) from Montana, USA is described as Parasitylenchus myiophagus n. sp. (Nematoda: Parasitylenchidae). The new species is characterized by the presence of an extremely long first generation female and numerous short and wide second generation males and females produced in “enclosed” clusters in the host’s body cavity. Both generation female nematodes are ovoviviparous, with short stylets lacking knobs and simple tails lacking spikes, palps or mucrons. The second generation males have paired, separate spicules, short stylets, and a bursa but no visible gubernaculum. The fly host shows evidence of demasculinization, which is attributed to nematode parasitism. The gonads of the second generation adults are infected with a microsporidium (Microsporidia), which is a new host record for tylenchid nematodes. A tylenchid-infected Baltic amber dolichopodid shows that associations between these two organisms extend back at least to the Eocene.